Evaluation of a tablet‐based assessment tool for measuring cognition among children 4–6 years of age in Ghana - Haiying Yuan; Maku Ocansey; Seth Adu‐Afarwuah; Margaret Sheridan; Amar Hamoudi; Harriet Okronipa; Sika M. Kumordzie; Brietta M. Oaks; Elizabeth Prado (Brain and Behavior, 2022)
Abstract Objectives To investigate several basic psychometric properties, including construct, convergent and discriminant validity, of the tablet‐based Rapid Assessment of Cognitive and Emotional Regulation (RACER) among children aged 4–6 years in Ghana. Methods We investigated whether RACER tasks administered to children in Ghana could successfully reproduce expected patterns of performance previously found in high‐income countries on similar tasks assessing inhibitory control (e.g., slower responses on inhibition trials), declarative memory (e.g., higher accuracy on previously seen items), and procedural memory (e.g., faster responses on sequence blocks). Next, we assessed the validity of declarative memory and inhibitory control scores by examining associations of these scores with corresponding paper‐based test scores and increasing child age. Lastly, we examined whether RACER was more sensitive than paper‐based tests to environmental risk factors common in low‐ and middle‐income countries (LMICs). Results Of the 966 children enrolled, more than 96% completed the declarative memory and inhibitory control tasks; however, around 30% of children were excluded from data analysis on the procedural memory task due to missing more than half of trials. The performance of children in Ghana replicated previously documented patterns of performance. RACER inhibitory control accuracy score was significantly correlated with child age (r (929) = .09, p = .007). However, our findings did not support other hypotheses. Conclusions The high task completion rates and replication of expected patterns support that certain RACER sub‐tasks are feasible for measuring child cognitive development in LMIC settings. However, this study did not provide evidence to support that RACER is a valid tool to capture meaningful individual differences among children aged 4–6 years in Ghana.